Nonaqueous electrolyte solution for lithium secondary battery and lithium secondary battery comprising same

CN119487665APending Publication Date: 2025-02-18LG ENERGY SOLUTION LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380051614.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-07-11
Filing Date
2023-07-05
Publication Date
2025-02-18

Smart Images

  • Figure BDA0005226070000000021
    Figure BDA0005226070000000021
  • Figure BDA0005226070000000041
    Figure BDA0005226070000000041
  • Figure BDA0005226070000000051
    Figure BDA0005226070000000051
Patent Text Reader

Abstract

The present invention relates to a non-aqueous electrolyte solution for a lithium secondary battery and a lithium secondary battery comprising the same, the non-aqueous electrolyte solution comprising a compound represented by Formula 1, a lithium salt, and an organic solvent.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application claims priority to Korean Patent Application No. 10-2022-0085281 filed on Jul. 11, 2022 and Korean Patent Application No. 10-2023-0086887 filed on Jul. 5, 2023, which are hereby incorporated by reference in their entirety.

[0002] The present invention relates to a non-aqueous electrolyte solution for a lithium secondary battery and a lithium secondary battery containing the same. Background Art

[0003] The preparation method of a lithium secondary battery is generally that, after forming an electrode assembly by disposing a separator between a positive electrode including a positive electrode active material formed of a lithium-containing transition metal oxide and a negative electrode including a negative electrode active material capable of storing lithium ions and inserting the electrode assembly into a battery casing, a non-aqueous electrolyte solution as a medium for transferring lithium ions is injected therein, and then the battery casing is sealed.

[0004] Since lithium secondary batteries can be miniaturized and have high energy density and operating voltage, they are being used in various fields such as mobile devices, electronic products, electric vehicles, etc. As the application fields of lithium secondary batteries diversify, the requirements for their physical performance conditions are gradually increasing. In particular, it is necessary to develop a lithium secondary battery that can operate stably even under high temperature conditions and has long life characteristics.

[0005] When a lithium secondary battery is operated under high temperature conditions, the PF 6- The anion may be thermally decomposed to generate a Lewis acid such as PF5, and it reacts with moisture to generate HF. The decomposition products such as PF5 and HF can not only destroy the film formed on the electrode surface, but also cause a decomposition reaction of the organic solvent, and can react with the decomposition product of the positive electrode active material to dissolve the transition metal ions, and the dissolved transition metal ions can be electrodeposited on the negative electrode to destroy the film formed on the negative electrode surface.

[0006] Since, as described above, if the electrolyte decomposition reaction continues on the damaged membrane, the performance of the battery further deteriorates, it is necessary to develop a secondary battery that can maintain excellent performance even under high temperature conditions. Summary of the invention

[0007] Technical issues

[0008] One aspect of the present invention provides a non-aqueous electrolyte solution and a lithium secondary battery comprising the non-aqueous electrolyte solution, which can form a stable film on the electrode and can control metal dissolution by including an R2-substituted pyrazole carboxylic acid derivative compound, and thus can help improve the performance of the lithium secondary battery.

[0009] Technical Solution

[0010] According to one aspect of the present invention, a non-aqueous electrolyte solution for a lithium secondary battery is provided, which includes: a lithium salt; an organic solvent; and a compound represented by Formula 1.

[0011] [Formula 1]

[0012]

[0013] In formula 1,

[0014] L1 is a direct bond or an alkylene group having 1 to 10 carbon atoms,

[0015] R1 is an alkyl group having 1 to 10 carbon atoms or a nitrile group,

[0016] L2 is a direct bond, an alkylene group having 1 to 10 carbon atoms, an alkyleneoxy group having 1 to 10 carbon atoms, or a sulfonyl group,

[0017] R2 is a fluorine-substituted or unsubstituted alkyl group having 1 to 10 carbon atoms, a nitrile group or an isocyanate group,

[0018] R3 is a fluorine-substituted or unsubstituted alkyl group having 1 to 10 carbon atoms,

[0019] n is any integer from 0 to 2, and when n is 2, two R3's are the same as or different from each other.

[0020] According to another aspect of the present invention, a lithium secondary battery is provided, comprising: a positive electrode including a positive electrode active material; a negative electrode including a negative electrode active material; a separator disposed between the positive electrode and the negative electrode; and the above-mentioned nonaqueous electrolyte solution for lithium secondary batteries.

[0021] Beneficial Effects

[0022] The non-aqueous electrolyte solution of the present invention can help improve the high temperature performance of lithium secondary batteries by including a compound represented by formula 1 having the function of strengthening the positive / negative electrode film and controlling the dissolution of metal. In particular, since the compound contains functional groups based on fluorine, sulfur and nitrogen in its structure, it can help improve the stability and safety of the battery by forming an organic / inorganic composite film. In addition, since nitrogen (N) and COO functional groups contained in the compound represented by formula 1 can interact with transition metals, it is possible to prevent the dissolved metal from being electro-deposited to the negative electrode, and ultimately a lithium secondary battery with improved electrochemical performance can be provided. DETAILED DESCRIPTION

[0023] Hereinafter, the present invention will be described in more detail.

[0024] Generally speaking, anions such as LiPF6 contained in lithium salts widely used in electrolyte solutions for lithium secondary batteries form decomposition products such as hydrogen fluoride (HF) and PF5 due to thermal decomposition or moisture. These decomposition products have acidic properties and can damage the film or electrode surface in the battery.

[0025] Due to the decomposition products of the electrolyte solution and the changes in the positive electrode structure caused by repeated charge and discharge, the transition metal in the positive electrode is easily dissolved into the electrolyte solution, and the dissolved transition metal is redeposited on the positive electrode to increase the resistance of the positive electrode. In addition, in the case where the dissolved transition metal moves to the negative electrode through the electrolyte solution, the dissolved transition metal is electrodeposited on the negative electrode to form dendrites, and may cause the destruction of the solid electrolyte interphase (SEI) film and additional electrolyte decomposition reactions, resulting in problems such as lithium ion consumption and increased resistance.

[0026] In addition, during the initial activation of the battery, a protective film is formed on the positive and negative electrodes by the reaction of the electrolyte solution, wherein, when the protective film becomes unstable due to the above reasons, the electrolyte solution undergoes additional decomposition during charge and discharge or high temperature exposure, causing battery degradation and gas generation.

[0027] In order to solve these problems, the inventors included the compound represented by Formula 1 in the non-aqueous electrolyte solution, and found that it has the effect of reducing the side reaction of the electrolyte solution at the positive electrode / negative electrode, and inhibiting the dissolution of transition metals, the generation of gas and the increase of battery resistance. In particular, in order to ensure high energy density, the increase of the operating voltage of the battery cell is inevitable, and when the operating voltage increases, the above-mentioned performance degradation problem may be further aggravated, wherein the use of the compound represented by Formula 1 can solve this problem.

[0028] Hereinafter, the respective components constituting the present invention will be described in more detail.

[0029] Non-aqueous electrolyte solution

[0030] The present invention provides a non-aqueous electrolyte solution for a lithium secondary battery, comprising: a lithium salt; an organic solvent; and a compound represented by Formula 1.

[0031] Hereinafter, each component will be described in detail.

[0032] (1) Compound represented by formula 1

[0033] The nonaqueous electrolyte solution of the present invention includes a compound represented by Formula 1 below.

[0034] [Formula 1]

[0035]

[0036] In formula 1,

[0037] L1 is a direct bond or an alkylene group having 1 to 10 carbon atoms,

[0038] R1 is an alkyl group having 1 to 10 carbon atoms or a nitrile group (-CN),

[0039] L2 is a direct bond, an alkylene group having 1 to 10 carbon atoms, an alkyleneoxy group having 1 to 10 carbon atoms, or a sulfonyl group (-SO2),

[0040] R2 is a fluorine-substituted or unsubstituted alkyl group having 1 to 10 carbon atoms, a nitrile group or an isocyanate group (-NCO),

[0041] R3 is a fluorine-substituted or unsubstituted alkyl group having 1 to 10 carbon atoms,

[0042] n is any integer between 0 and 2, and when n is 2, two R3's are the same as or different from each other.

[0043] Since the compound represented by Formula 1 contains an unshared electron pair in the ester (-COO-) and a bond (NN) between nitrogen in the pyrazole, a stable film can be formed by strong binding to the transition metal on the positive electrode surface. In addition, since the compound represented by Formula 1 can bind to metal ions through unshared electron pairs even in an electrolyte solution, electrodeposition on the negative electrode can be prevented in advance. In addition, in the case of an ester functional group as shown in Formula 1 of the present application, due to the excellent ability to move lithium (Li) through unshared electron pairs of oxygen during film formation, it is desirable to be able to form a film that helps to improve battery output compared to a structure in which a sulfonyl or fluorine (F) substituent is directly substituted on pyrazole.

[0044] In an embodiment of the present invention, R1 in Formula 1 may be an alkyl group having 1 to 5 carbon atoms or a nitrile group, and specifically may be a methyl group or a nitrile group. In the case where hydrogen is substituted with an alkyl group or a nitrile group at the R1 position, the H + The increase in can suppress the acidification of the electrolyte solution and the side reactions caused thereby, thus having the effect of improving the battery durability. In particular, in the case of substitution with a nitrile group, it is more preferable that a metal ion scavenging effect can be additionally expected by the unshared electron pair.

[0045] In an embodiment of the present invention, R2 in Formula 1 is an alkyl group having 1 to 5 carbon atoms, a fluoroalkyl group having 1 to 5 carbon atoms, or an isocyanate group, preferably a methyl group, a trifluoromethyl group, or an isocyanate group. In the case where R2 is hydrogen, there is a + The deprotonation removed from -COOH causes an increase in the acidity of the electrolyte solution.

[0046] In an embodiment of the present invention, R3 in Formula 1 may be a fluorine-substituted alkyl group having 1 to 10 carbon atoms, particularly a fluorine-substituted alkyl group having 1 to 5 carbon atoms, and more particularly a trifluoromethyl group.

[0047] In an embodiment of the present invention, n in Formula 1 may be 0 or 1, preferably n=1. Compared with the case where n=0 in Formula 1, in the case where n=1, a film with improved high temperature performance can be formed. Specifically, if fluorine is contained in the structure, the oxidation stability is improved, which means that a stable film can be formed on the positive electrode. If an unstable film is formed on the positive electrode, the performance may deteriorate due to the decomposition reaction of the electrolyte solution at a high voltage, and it has the effect of preventing the degradation. In addition, since a fluorine-containing film is formed during the reduction process at the negative electrode, it can be compounded with an organic film formed by pyrazole to form an organic / inorganic composite film. That is, it is desirable to form an SEI in which the life performance improvement effect of the organic film and the advantages of the strong durability of the inorganic film are achieved together.

[0048] In an embodiment of the present invention, the compound represented by Formula 1 may be represented by the following Formula 1-1 or Formula 1-2.

[0049] [Formula 1-1]

[0050]

[0051] [Formula 1-2]

[0052]

[0053] In formula 1-1 and formula 1-2,

[0054] R1 to R3 are as defined in Formula 1.

[0055] In an embodiment of the present invention, Formula 1 may be represented by any one of the following Formulas 1A to 1F.

[0056] [Formula 1A]

[0057]

[0058] [Formula 1B]

[0059]

[0060] [Formula 1C]

[0061]

[0062] [Formula 1D]

[0063]

[0064] [Formula 1E]

[0065]

[0066] [Formula 1F]

[0067]

[0068] In an embodiment of the present invention, the amount of the compound represented by Formula 1 may be 0.01 to 15 wt %, preferably 0.03 to 12 wt %, more preferably 0.05 to 10 wt %, based on the total weight of the nonaqueous electrolyte solution.

[0069] When the amount of the compound represented by Formula 1 is 0.01 wt % or more, the above-mentioned effects can be achieved, and when the amount is 15 wt % or less, it is desirable to prevent the decrease in ionic conductivity of the nonaqueous electrolyte solution and the formation of an uneven film on the electrode surface or an increase in side reactions.

[0070] (2) Additives

[0071] In order to prevent the electrolyte solution from decomposing under high voltage environment and causing electrode collapse, or to further improve low-temperature high-rate discharge characteristics, high-temperature stability, overcharge protection, and battery expansion inhibition effect at high temperature, the non-aqueous electrolyte solution of the present invention may optionally further include the following additives if necessary.

[0072] The additive may be at least one selected from the group consisting of cyclic carbonate compounds, sultone compounds, sulfate compounds, phosphorus compounds, nitrile compounds, amine compounds, silane compounds, benzene compounds and lithium salt compounds.

[0073] The cyclic carbonate-based compound may be at least one selected from the group consisting of vinylene carbonate (VC), vinyl ethylene carbonate (VEC), and fluoroethylene carbonate (FEC), and may specifically be vinylene carbonate.

[0074] The sultone compound is a material that can form a stable SEI film through a reduction reaction on the surface of the negative electrode, wherein the sultone compound can be at least one compound selected from the group consisting of 1,3-propane sultone (PS), 1,4-butane sultone, ethane sultone, 1,3-propene sultone (PRS), 1,4-butene sultone and 1-methyl-1,3-propene sultone, and specifically can be 1,3-propane sultone (PS).

[0075] The sulfate / ester compound is a material that can be electrolyzed on the surface of the negative electrode to form a stable SEI film that does not crack even during high-temperature storage, wherein the sulfate / ester compound can be selected from at least one of the group consisting of ethylene sulfate (Esa), trimethylene sulfate (TMS) or methyl trimethylene sulfate (MTMS).

[0076] The phosphorus compound may be a phosphate or phosphite compound, and specifically, may be at least one selected from the group consisting of tris(trimethylsilyl)phosphate, tris(trimethylsilyl)phosphite, tris(2,2,2-trifluoroethyl)phosphate and tris(trifluoroethyl)phosphite.

[0077] The nitrile compound may be at least one selected from the group consisting of succinonitrile (SN), adiponitrile (ADN), acetonitrile, propionitrile, butyronitrile, valeronitrile, octanonitrile, heptanenitrile, cyclopentanenitrile, cyclohexanenitrile, 2-fluorobenzonitrile, 4-fluorobenzonitrile, difluorobenzonitrile, trifluorobenzonitrile, benzyl cyanide, 2-fluorophenyl acetonitrile, 4-fluorophenyl acetonitrile, ethylene glycol bis(2-cyanoethyl) ether (ASA3), 1,3,6-hexanetonitrile (HTCN), 1,4-dicyano-2-butene (DCB) and 1,2,3-tris(2-cyanoethyl)propane (TCEP).

[0078] The amine compound may be at least one selected from the group consisting of triethanolamine and ethylenediamine, and the silane compound may be tetravinylsilane.

[0079] The benzene compound may be at least one selected from the group consisting of monofluorobenzene, difluorobenzene, trifluorobenzene, and tetrafluorobenzene.

[0080] The lithium salt compound is a compound different from the lithium salt contained in the non-aqueous electrolyte solution, wherein the lithium salt compound can be at least one compound selected from the group consisting of lithium difluorophosphate (LiDFP; LiPO2F2), lithium bis(oxalate)borate (LiBOB; LiB(C2O4)2), lithium tetrafluoroborate (LiBF4), lithium tetraphenylborate and lithium difluorobis(oxalate)phosphate (LiDFOP).

[0081] Preferably, the non-aqueous electrolyte solution of an embodiment of the present invention may further include at least one additive selected from the group consisting of vinylene carbonate (VC), vinyl ethylene carbonate (VEC), 1,3-propane sultone (PS), ethylene sulfate (ESa), lithium tetrafluoroborate (LiBF4), lithium difluoro (oxalate) borate (LiODFB) and lithium difluorophosphate (LiDFP), and may more preferably include vinyl ethylene carbonate (VEC). In this case, the decomposition of the compound represented by Formula 1 of the present invention is suppressed by rapid film formation on the positive and negative electrodes, and there is an effect of increasing the residual amount of the compound that can be combined with PF5. This is an effect caused by the unshared electron pair of nitrogen in the pyrazole structure. Since the unshared electron pair in the pyrazole structure acts as a Lewis base, further decomposition of PF5 (Lewis acid) can be prevented in advance. Since the decomposition of the Lewis acid causes the side reaction of the electrode film and the resistance increase caused by the byproducts, it may be a factor in the degradation of battery performance.

[0082] The amount of the additive may be 0.1 wt % to 10 wt %, preferably 0.3 wt % to 5 wt %, more preferably 0.3 wt % to 1 wt %, based on the total weight of the nonaqueous electrolyte solution. When the amount of the additive is within the above range, it has the effect of suppressing side reactions by forming a film on the positive electrode and the negative electrode.

[0083] (3) Organic solvents

[0084] The nonaqueous electrolyte solution of the present invention includes an organic solvent.

[0085] Can use the various organic solvents that are generally used for lithium electrolyte as organic solvent, and without restriction.For example, organic solvent can be cyclic carbonate solvent, linear carbonate solvent, linear ester solvent, cyclic ester solvent, nitrile solvent or its mixture, can preferably comprise at least two kinds of mixtures in the group being selected from by cyclic carbonate solvent, linear carbonate solvent and linear ester solvent, and can more preferably comprise the mixture of cyclic carbonate solvent and linear carbonate solvent.

[0086] The cyclic carbonate solvent can dissociate the lithium salt in the electrolyte into a highly viscous organic solvent well due to its high dielectric constant, wherein the cyclic carbonate solvent can be at least one selected from the group consisting of ethylene carbonate (EC), propylene carbonate (PC), 1,2-butylene carbonate, 2,3-butylene carbonate, 1,2-pentylene carbonate, 2,3-pentylene carbonate and vinylene carbonate, and preferably can include ethylene carbonate (EC) or propylene carbonate (PC).

[0087] In addition, the linear carbonate solvent is an organic solvent with low viscosity and low dielectric constant, wherein the linear carbonate solvent can be at least one selected from the group consisting of dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate, ethyl methyl carbonate (EMC), methyl propyl carbonate and ethyl propyl carbonate, and can preferably include ethyl methyl carbonate (EMC), dimethyl carbonate (DMC) or diethyl carbonate (DEC).

[0088] In order to prepare an electrolyte solution having high ion conductivity, it is desirable to use a mixture of a cyclic carbonate-based solvent and a chain carbonate-based solvent as the organic solvent.

[0089] The chain ester solvent may be at least one selected from the group consisting of methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, and butyl propionate, and may preferably be methyl propionate, ethyl propionate, or propyl propionate.

[0090] The cyclic ester solvent may be at least one selected from the group consisting of γ-butyrolactone, γ-valerolactone, γ-caprolactone, σ-valerolactone, and ε-caprolactone.

[0091] The nitrile solvent may be at least one selected from the group consisting of succinonitrile, acetonitrile, propionitrile, butyronitrile, valeronitrile, octanonitrile, heptanenitrile, cyclopentanenitrile, cyclohexanenitrile, 2-fluorobenzonitrile, 4-fluorobenzonitrile, difluorobenzonitrile, trifluorobenzonitrile, benzyl cyanide, 2-fluorobenzoyl cyanide and 4-fluorobenzoyl cyanide, and may preferably be succinonitrile.

[0092] The total weight of the non-aqueous electrolyte solution except for the organic solvent, for example, the remainder other than the amount of the compound represented by Formula 1, the additive and the lithium salt may all be the organic solvent, unless otherwise specified.

[0093] (4) Lithium salt

[0094] The nonaqueous electrolyte solution of the present invention includes a lithium salt.

[0095] Any lithium salt generally used in an electrolyte solution for a lithium secondary battery may be used as the lithium salt without limitation, and, specifically, the lithium salt may include Li +as a cation, and may include at least one selected from the group consisting of: F - , Cl - Br - ,I - 、NO3 - 、N(CN)2 - 、BF4 - 、ClO4 - , B 10 Cl 10 - 、AlCl4 - 、AlO4 - PF6 - CF3SO3 - 、CH3CO2 - CF3CO2 - 、AsF6 - 、SbF6 - 、CH3SO3 - 、(CF3CF2SO2)2N - 、(CF3SO2)2N - 、(FSO2)2N - 、BF2C2O4 - , BC4O8 - 、BF2C2O4CHF - PF4C2O4 - PF2C4O8 - PO2F2 - 、(CF3)2PF4 - 、(CF3)3PF3 - 、(CF3)4PF2 - 、(CF3)5PF - 、(CF3)6P - 、C4F9SO3 - CF3CF2SO3 - CF3CF2(CF3)2CO - 、(CF3SO2)2CH - CF3(CF2)7SO3 - and SCN - .

[0096] Specifically, the lithium salt may be at least one selected from the group consisting of LiPF6, LiClO4, LiBF4, lithium bis(fluorosulfonyl)imide (LiN(FSO2)2; LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium bis(pentafluoroethanesulfonyl)imide (LiBETI), lithium trifluoromethanesulfonate (LiSO3CF3), lithium difluorophosphate (LiPO2F2), lithium bis(oxalate)borate (LiBOB), lithium difluoro(oxalate)borate (LiFOB), lithium difluoro(bisoxalate)phosphate (LiDFOP), lithium tetrafluoro(oxalate)phosphate (LiTFOP) and lithium fluoromalonate (difluoro)borate (LiFMDFB), and may preferably be LiPF6.

[0097] In an embodiment of the present invention, in the non-aqueous organic solution containing a lithium salt and an organic solvent, the concentration of the lithium salt may be 0.5 to 4.0 M, specifically 0.5 to 3.0 M, and more specifically 0.8 to 2.0 M. When the lithium salt concentration is within the above range, appropriate electrolyte impregnation can be obtained by preventing excessive increases in viscosity and surface tension while sufficiently ensuring the effects of improving low-temperature output and improving cycle characteristics.

[0098] Lithium secondary battery

[0099] Next, the lithium secondary battery of the present invention will be described.

[0100] The lithium secondary battery of the present invention includes: a positive electrode containing a positive electrode active material, a negative electrode containing a negative electrode active material, a separator disposed between the positive electrode and the negative electrode, and a non-aqueous electrolyte solution. In this case, the non-aqueous electrolyte solution is the above-mentioned non-aqueous electrolyte solution of the present invention. Since the non-aqueous electrolyte solution has been described above, its description will be omitted, and other components will be described below.

[0101] (1) Positive electrode

[0102] The positive electrode of the present invention includes a positive electrode active material, and may be prepared by coating a positive electrode collector with a positive electrode slurry including the positive electrode active material, a binder, a conductive agent, and a solvent, and then drying and roll-pressing the coated positive electrode collector.

[0103] The positive electrode collector is not particularly limited as long as it has conductivity without causing adverse chemical changes in the battery, and for example, stainless steel, aluminum, nickel, titanium, fired carbon, or aluminum or stainless steel surface-treated with carbon, nickel, titanium, silver, etc. can be used.

[0104] The positive electrode active material is a compound capable of reversibly intercalating and deintercalating lithium. Among them, the positive electrode active material may be at least one selected from the group consisting of LCO (LiCoO2), LNO (LiNiO2), LMO (LiMnO2), LiMn2O4, LiCoPO4, LFP (LiFePO4), and lithium composite transition metal oxides containing nickel (Ni), cobalt (Co), and manganese (Mn). For example, the positive electrode active material may be a lithium-nickel-manganese-cobalt-based oxide represented by Li(Ni p Co q Mn r1 )O2 (0 < p < 1, 0 < q < 1, 0 < r1 < 1, and p + q + r1 = 1), a lithium-nickel-manganese-cobalt-based oxide represented by Li(Ni p1 Co q1 Mn r2 )O4 (0 < p1 < 2, 0 < q1 < 2, 0 < r2 < 2, and p1 + q1 + r2 = 2), or a lithium-nickel-cobalt-transition metal (M) oxide represented by Li(Ni p2 Co q2 Mn r3 M S2 )O2 (M is selected from the group consisting of aluminum (Al), iron (Fe), vanadium (V), chromium (Cr), titanium (Ti), tantalum (Ta), magnesium (Mg), and molybdenum (Mo), and 0 < p2 < 1, 0 < q2 < 1, 0 < r3 < 1, 0 < S2 < 1, and p2 + q2 + r3 + S2 = 1).

[0105] The molar ratio of nickel in the positive electrode active material to the transition metal may be 60 mol% or more, preferably 70 mol% or more, and more preferably 80 mol% or more.

[0106] In an embodiment of the present invention, the lithium composite transition metal oxide may be a compound represented by the following formula 2. That is, the positive electrode active material in the embodiment of the present invention may include the lithium composite transition metal oxide represented by the following formula 2.

[0107] [Formula 2]

[0108] Li 1+x (Ni a Co b Mn c M d )O2

[0109] In Formula 2,

[0110] M is at least one selected from the group consisting of tungsten (W), copper (Cu), Fe, V, Cr, Ti, zirconium (Zr), zinc (Zn), aluminum (Al), indium (In), Ta, yttrium (Y), lanthanum (La), strontium (Sr), gallium (Ga), scandium (Sc), gadolinium (Gd), samarium (Sm), calcium (Ca), cerium (Ce), niobium (Nb), Mg, boron (B), and Mo.

[0111] 1 + x, a, b, c, and d are atomic fractions of each independent element,

[0112] wherein, -0.2 ≤ x ≤ 0.2, 0.6 ≤ a < 1, 0 < b ≤ 0.3, 0 < c ≤ 0.3, 0 ≤ d ≤ 0.1, and a + b + c + d = 1.

[0113] 1 + x represents the molar ratio of lithium in the lithium composite transition metal oxide, wherein x can satisfy -0.1 ≤ x ≤ 0.2 or 0 ≤ x ≤ 0.2. When the molar ratio of lithium satisfies the above range, the crystal structure of the lithium composite transition metal oxide can be stably formed.

[0114] a represents the molar ratio of nickel in all metals except lithium in the lithium composite transition metal oxide, wherein a can satisfy 0.70 ≤ a < 1, 0.75 ≤ a < 1, or 0.80 ≤ a < 1. When the molar ratio of nickel satisfies the above range, high capacity can be achieved because high energy density can be exhibited.

[0115] b represents the molar ratio of cobalt in all metals except lithium in the lithium composite transition metal oxide, wherein b can satisfy 0 < b ≤ 0.20, 0 < b ≤ 0.18, or 0 < b ≤ 0.15. When the molar ratio of cobalt satisfies the above range, good resistance characteristics and output characteristics can be obtained.

[0116] c represents the molar ratio of manganese in all metals except lithium in the lithium composite transition metal oxide, wherein c can satisfy 0 < c ≤ 0.20, 0 < c ≤ 0.18, or 0 < c ≤ 0.15. When the molar ratio of manganese satisfies the above range, the structural stability of the positive electrode active material is excellent.

[0117] In an embodiment of the present invention, the lithium composite transition metal oxide may include at least one doping element selected from the group consisting of W, Cu, Fe, V, Cr, Ti, Zr, Zn, Al, In, Ta, Y, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B, and Mo. In other words, d representing the molar ratio of the doping element in all metals except lithium in the lithium composite transition metal oxide can satisfy 0 < d ≤ 0.10, 0 < d ≤ 0.08, or 0 < d ≤ 0.05.

[0118] Preferably, a, b, c, and d in Formula 2 may respectively satisfy 0.70 ≤ a < 1, 0 < b ≤ 0.2, 0 < c ≤ 0.2, and 0 ≤ d ≤ 0.1.

[0119] In another embodiment of the present invention, the lithium composite transition metal oxide may be selected from the group consisting of Li p Mn 1-q M q A2, Li p Mn2O 4-r X r 、Li p Mn 2-q M q M’ r A4, Li p Co 1-q M q A2, Li p Co 1-q M q O 2-r X r 、Li p Ni 1-q M q O 2-r X r 、Li p Ni 1-q Co q O 2- r X r 、Li p Ni 1-q-r Co q M r A w 、Li p Ni 1-q-r Co q M r O 2-w X w 、Li p Ni 1-q-r Mn q M r A w 和Li p Ni 1-q-r Mn q M r O 2-w X wAt least one of the group consisting of, wherein p, q, r, w satisfy 0.9≤p≤1.2, 0≤q≤1, 0≤r≤1 and 0≤w≤2, respectively, M and M' are the same as or different from each other and are one or more elements selected from the group consisting of Mg, Al, Co, potassium (K), sodium (Na), Ca, silicon (Si), Ti, tin (Sn), V, germanium (Ge), Ga, B, arsenic (As), Zr, Mn, Cr, Fe, Sr, V and rare earth elements, A is at least one element selected from the group consisting of oxygen (O), F, sulfur (S) and phosphorus (P), and X is at least one element selected from the group consisting of F, S, and P.

[0120] The content of the positive electrode active material may be 80 wt % to 99 wt %, specifically 90 wt % to 99 wt %, based on the total weight of the solids in the positive electrode slurry. When the content of the positive electrode active material is less than 80 wt %, the capacity may be reduced due to the reduced energy density.

[0121] The binder is a component that assists the bonding between the active material and the conductive agent and the bonding with the current collector, wherein the binder is generally added in an amount of 1 wt % to 30 wt % based on the total weight of the solids in the positive electrode slurry. Examples of the binder may be polyvinylidene fluoride, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene monomer, sulfonated ethylene-propylene-diene monomer, styrene-butadiene rubber, fluororubber or various copolymers thereof.

[0122] In addition, the conductive agent is a material that provides conductivity without causing adverse chemical changes in the battery, wherein the conductive agent may be added in an amount of 0.5 wt % to 20 wt % based on the total weight of the solids in the positive electrode slurry.

[0123] For example, the conductive agent can be selected from the following conductive materials: for example, carbon black, such as acetylene black, Ketjen black, channel black, furnace black, lamp black and thermal black; graphite powder, such as natural graphite, artificial graphite, carbon nanotubes and graphite; conductive fibers, such as carbon fibers and metal fibers; conductive powders, such as carbon fluoride powder, aluminum powder and nickel powder; conductive whiskers, such as zinc oxide whiskers and potassium titanate whiskers; conductive metal oxides, such as titanium oxide; and polyphenylene derivatives.

[0124] In addition, the solvent of the positive electrode slurry may include an organic solvent such as N-methyl-2-pyrrolidone (NMP), and its amount may be such that the desired viscosity is obtained when the positive electrode active material, the binder and the conductive agent are included. For example, the amount of solvent added may be such that the concentration of the solids in the positive electrode slurry including the positive electrode active material, the binder and the conductive agent is 40 wt % to 90 wt %, preferably 50 wt % to 80 wt %.

[0125] (2) Negative electrode

[0126] The negative electrode of the present invention includes a negative electrode active material, and may be prepared by coating a negative electrode collector with a negative electrode slurry including the negative electrode active material, a binder, a conductive agent, and a solvent, and then drying and roll-pressing the coated negative electrode collector.

[0127] The thickness of the negative electrode collector is generally 3 μm to 500 μm. The negative electrode collector is not particularly limited as long as it has high conductivity without causing adverse chemical changes in the battery, and can use, for example, copper, stainless steel, aluminum, nickel, titanium, fired carbon, copper or stainless steel surface-treated with carbon, nickel, titanium, silver, etc.; or aluminum-cadmium alloy. In addition, similar to the positive electrode collector, the negative electrode collector can have fine surface roughness to improve the bonding strength with the negative electrode active material, and the negative electrode collector can be used in various shapes, such as films, sheets, foils, nets, porous bodies, foams, non-woven fabrics, etc.

[0128] In addition, the negative electrode active material may include at least one selected from the group consisting of a carbon material capable of reversibly intercalating / deintercalating lithium ions, a metal or an alloy of lithium and the metal, a metal composite oxide, a material doped or dedoped with lithium, lithium metal, and a transition metal oxide.

[0129] As a carbon material capable of reversibly embedding / de-embedding lithium ions, a carbon-based negative electrode active material commonly used in lithium ion secondary batteries can be used without particular limitation, and as a typical example, crystalline carbon and / or amorphous carbon can be used. Examples of crystalline carbon can be graphites such as irregular, planar, flaky, spherical or fibrous natural graphite or artificial graphite, and examples of amorphous carbon can be soft carbon (low temperature sintered carbon) or hard carbon, mesophase pitch carbide and fired coke.

[0130] As the metal or the alloy of lithium and the metal, a metal selected from the group consisting of copper (Cu), nickel (Ni), sodium (Na), potassium (K), rubidium (Rb), cesium (Cs), francium (Fr), beryllium (Be), magnesium (Mg), calcium (Ca), strontium (Sr), silicon (Si), antimony (Sb), lead (Pb), indium (In), zinc (Zn), barium (Ba), radium (Ra), germanium (Ge), aluminum (Al) and tin (Sn), or an alloy of lithium and the metal can be used.

[0131] As the metal composite oxide, PbO, PbO2, Pb2O3, Pb3O4, Sb2O3, Sb2O4, Sb2O5, GeO, GeO2, Bi2O3, Bi2O4, Bi2O5, Li x Fe2O3(0≤x≤1), Li x WO2(0≤x≤1) and Snx Me 1-x Me' y O z (Me: Mn, Fe, Pb or Ge; Me': Al, B, P, Si, elements of Group I, Group II and Group III in the periodic table, or a halogen; 0 < x ≤ 1; 1 ≤ y ≤ 3; 1 ≤ z ≤ 8) at least one selected from the group consisting of.

[0132] The material that can be doped or undoped with lithium can include Si, SiO x (0 < x < 2), Si - Y alloy (where Y is an element selected from the group consisting of alkali metals, alkaline earth metals, Group 13 elements, Group 14 elements, transition metals, rare earth elements and combinations thereof, and is not Si), Sn, SnO2 and Sn - Y (where Y is an element selected from the group consisting of alkali metals, alkaline earth metals, Group 13 elements, Group 14 elements, transition metals, rare earth elements and combinations thereof, and is not Sn), and mixtures of SiO2 and at least one of them can also be used. Element Y can be selected from the group consisting of Mg, Ca, Sr, Ba, Ra, Sc, Y, Ti, Zr, hafnium (Hf), V, Nb, Ta, Cr, Mo, W, technetium (Tc), rhenium (Re), Fe, Pb, ruthenium (Ru), osmium (Os), rhodium (Rh), iridium (Ir), palladium (Pd), platinum (Pt), Cu, silver (Ag), gold (Au), Zn, cadmium (Cd), B, Al, Ga, Sn, In, Ge, P, As, Sb, bismuth (Bi), S, selenium (Se), tellurium (Te), polonium (Po) and combinations thereof.

[0133] Examples of transition metal oxides can be lithium - containing titanium composite oxide (LTO), vanadium oxide and lithium vanadium oxide.

[0134] In an embodiment of the present invention, the negative electrode active material can be a mixture of a carbon - based material and a silicon - based material, and can preferably be a mixture of graphite and SiO.

[0135] Based on the total weight of the solids in the negative electrode slurry, the content of the negative electrode active material can be 80 wt% to 99 wt%.

[0136] The binder is a component that assists the bonding between the conductive agent, the active material and the current collector, wherein the binder is generally added in an amount of 1 wt % to 30 wt % based on the total weight of the solids in the negative electrode slurry. Examples of the binder may be polyvinylidene fluoride, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene monomer, sulfonated ethylene-propylene-diene monomer, styrene-butadiene rubber, fluororubber or various copolymers thereof.

[0137] The conductive agent is a component for further improving the conductivity of the negative electrode active material, wherein the conductive agent is added in an amount of 0.5 wt % to 20 wt % based on the total weight of the solids in the negative electrode slurry. Any conductive agent can be used without particular limitation as long as it has conductivity and does not cause adverse chemical changes to the battery, for example, the following conductive materials can be used, for example: carbon black, such as acetylene black, ketjen black, channel black, furnace black, lamp black or thermal black; graphite powder, such as natural graphite with a well-developed crystal structure, artificial graphite, carbon nanotubes or graphite; conductive fibers, such as carbon fibers or metal fibers; conductive powders, such as carbon fluoride powders, aluminum powders or nickel powders; conductive whiskers, such as zinc oxide whiskers or potassium titanate whiskers; conductive metal oxides, such as titanium oxide; or polyphenylene derivatives.

[0138] The solvent of the negative electrode slurry may include: water; or an organic solvent such as NMP and ethanol, and its amount may be such that the desired viscosity is obtained when the negative electrode active material, the binder and the conductive agent are included. For example, the amount of solvent added may be such that the solid content of the slurry including the negative electrode active material, the binder and the conductive agent is 30 wt % to 80 wt %, preferably 40 wt % to 70 wt %.

[0139] (3) Diaphragm

[0140] The lithium secondary battery of the present invention includes a separator between a positive electrode and a negative electrode.

[0141] The separator separates the negative electrode and the positive electrode and provides a path for the movement of lithium ions. Any separator can be used without particular limitation as long as it is a separator commonly used in lithium secondary batteries. In particular, a separator having high moisture retention capacity for electrolyte solution, excellent safety, and low resistance to electrolyte ion transfer can be used.

[0142] Specifically, a porous polymer film can be used, for example, a porous polymer film prepared from a polyolefin polymer (e.g., ethylene homopolymer, propylene homopolymer, ethylene / butene copolymer, ethylene / hexene copolymer, and ethylene / methacrylate copolymer); or a laminated structure having more than two layers. In addition, a typical porous non-woven fabric can be used, for example, a non-woven fabric formed of high melting point glass fiber or polyethylene terephthalate fiber. In addition, a coated diaphragm including a ceramic component or a polymer material can be used to ensure heat resistance or mechanical strength, and a diaphragm having a single-layer or multi-layer structure can be used.

[0143] As described above, the lithium secondary battery of the present invention can be suitably used in portable devices such as mobile phones, notebook computers, and digital cameras, and electric vehicles such as hybrid electric vehicles (HEVs).

[0144] Therefore, according to another embodiment of the present invention, a battery module including the above-mentioned lithium secondary battery as a unit cell and a battery pack including the battery module are provided.

[0145] The battery module or battery pack may be used as a power source for at least one of the following medium- to large-sized devices: a power tool; an electric vehicle including an electric vehicle (EV), a hybrid electric vehicle (HEV), and a plug-in hybrid electric vehicle (PHEV); or a power storage system.

[0146] The shape of the lithium secondary battery of the present invention is not particularly limited, but a cylindrical shape using a can, a prismatic shape, a pouch shape, or a coin shape may be used.

[0147] The lithium secondary battery of the present invention can be used not only in a battery cell as a power source for small devices but also as a unit cell in a large or medium-sized battery module including a plurality of battery cells.

[0148] Hereinafter, the present invention will be described in detail according to specific embodiments.

[0149] Example: Preparation of lithium secondary battery

[0150] Example 1

[0151] 1) Preparation of non-aqueous electrolyte solution

[0152] After mixing ethylene carbonate (EC): ethyl methyl carbonate (EMC) at a volume ratio of 30:70, a non-aqueous organic solution was prepared by dissolving LiPF6 so that the concentration of LiPF6 was 1 M. A 100 wt % non-aqueous electrolyte solution was prepared by mixing 0.05 wt % of the compound represented by Formula 1A with the remaining non-aqueous organic solution.

[0153] 2) Preparation of lithium secondary batteries

[0154] As the positive electrode active material, Li(Ni 0.8 Co 0.1 Mn 0.1 )O2, conductive agent (carbon black), binder (polyvinylidene fluoride) and N-methyl-2-pyrrolidone (NMP) were added in a mass ratio of 98:1:1 to prepare a positive electrode slurry (solid content: 60 wt%). A 15 μm thick aluminum (Al) film was used as a positive electrode current collector, coated with the positive electrode slurry, dried, and then rolled to form a positive electrode.

[0155] Graphite was used as the negative electrode active material, SBR-CMC was used as the binder, and carbon black was used as the conductive agent, which were added to water as the solvent at a mass ratio of 95:3.5:1.5 to prepare a negative electrode slurry (solid content: 60 wt%). A 10 μm thick copper (Cu) film was used as the negative electrode current collector, which was coated with the negative electrode slurry, dried, and then rolled to prepare the negative electrode.

[0156] The electrode assembly was prepared by sequentially stacking a positive electrode, a polyolefin-based porous separator coated with inorganic particles (Al2O3), and a negative electrode.

[0157] The prepared electrode assembly was loaded into a pouch-type battery case, and the nonaqueous electrolyte solution prepared above was injected therein to prepare a lithium secondary battery.

[0158] Example 2

[0159] A lithium secondary battery was prepared in the same manner as in Example 1, except that 0.5 wt % of vinyl ethylene carbonate (VEC) was further added during the preparation of the nonaqueous electrolyte solution.

[0160] Example 3

[0161] A lithium secondary battery was prepared in the same manner as in Example 1, except that the amount of the compound represented by Formula 1A was changed to 10 wt % during the preparation of the nonaqueous electrolyte solution.

[0162] Example 4

[0163] A lithium secondary battery was prepared in the same manner as in Example 3, except that 0.5 wt % of vinyl ethylene carbonate (VEC) was further added during the preparation of the nonaqueous electrolyte solution.

[0164] Example 5

[0165] A lithium secondary battery was prepared in the same manner as in Example 1, except that the compound represented by Formula 1B was used instead of the compound represented by Formula 1A during the preparation of the nonaqueous electrolyte solution.

[0166] Example 6

[0167] A lithium secondary battery was prepared in the same manner as in Example 5, except that the amount of the compound represented by Formula 1B was changed to 10 wt % during the preparation of the nonaqueous electrolyte solution.

[0168] Example 7

[0169] A lithium secondary battery was prepared in the same manner as in Example 1, except that the compound represented by Formula 1C was used instead of the compound represented by Formula 1A during the preparation of the nonaqueous electrolyte solution.

[0170] Example 8

[0171] A lithium secondary battery was prepared in the same manner as in Example 7, except that the amount of the compound represented by Formula 1C was changed to 10 wt % during the preparation of the nonaqueous electrolyte solution.

[0172] Example 9

[0173] A lithium secondary battery was prepared in the same manner as in Example 1, except that the compound represented by Formula 1D was used instead of the compound represented by Formula 1A during the preparation of the nonaqueous electrolyte solution.

[0174] Example 10

[0175] A lithium secondary battery was prepared in the same manner as in Example 1, except that the compound represented by Formula 1E was used instead of the compound represented by Formula 1A during the preparation of the nonaqueous electrolyte solution.

[0176] Embodiment 11

[0177] A lithium secondary battery was prepared in the same manner as in Example 1, except that the compound represented by Formula 1F was used instead of the compound represented by Formula 1A during the preparation of the nonaqueous electrolyte solution.

[0178] Comparative Example 1

[0179] A lithium secondary battery was prepared in the same manner as in Example 1, except that the compound represented by Formula 1A was not added during the preparation of the nonaqueous electrolyte solution.

[0180] Comparative Example 2

[0181] A lithium secondary battery was prepared in the same manner as in Comparative Example 1, except that 0.5 wt % of vinyl ethylene carbonate (VEC) was further added during the preparation of the nonaqueous electrolyte solution.

[0182] Comparative Example 3

[0183] A lithium secondary battery was prepared in the same manner as in Example 1, except that the compound represented by Formula 1A was replaced with a compound represented by the following Formula Z1 during the preparation of the nonaqueous electrolyte solution.

[0184] [Formula Z1]

[0185]

[0186] Comparative Example 4

[0187] A lithium secondary battery was prepared in the same manner as in Comparative Example 3, except that the amount of the compound represented by Formula Z1 was changed to 10 wt % during the preparation of the nonaqueous electrolyte solution.

[0188] Comparative Example 5

[0189] A lithium secondary battery was prepared in the same manner as in Example 1, except that the compound represented by Formula 1A was replaced with a compound represented by the following Formula Z2 during the preparation of the nonaqueous electrolyte solution.

[0190] [Formula Z2]

[0191]

[0192] Comparative Example 6

[0193] A lithium secondary battery was prepared in the same manner as in Comparative Example 5, except that the amount of the compound represented by Formula Z2 was changed to 10 wt % during the preparation of the nonaqueous electrolyte solution.

[0194] Comparative Example 7

[0195] A lithium secondary battery was prepared in the same manner as in Example 1, except that the compound represented by Formula 1A was replaced with a compound represented by the following Formula Z3 during the preparation of the nonaqueous electrolyte solution.

[0196] [Formula Z3]

[0197]

[0198] <Experimental Example: Battery Performance Evaluation>

[0199] Experimental Example 1: Measurement of Capacity and Resistance after High-Temperature Storage

[0200] After the formation process is performed on the lithium secondary battery prepared in the embodiment and the comparative example, it is charged (0.05C cut-off) to 4.25V at a constant current / constant voltage (CC / CV) rate of 0.33C at 25°C, and discharged to 2.50V at a constant current (CC) rate of 0.33C, and then the initial discharge capacity is measured. The charging state is set to a charging state (SOC) of 50% based on the measured discharge capacity, and the voltage drop generated when a discharge pulse is applied for 10 seconds at a constant current of 2.5C is measured, thereby determining the initial resistance.

[0201] Afterwards, each battery was fully charged to 100% SOC under the same conditions and stored at high temperature (60°C) for 8 weeks. Then, each battery was placed in a charger and discharger at room temperature (25°C), and the capacity and resistance were measured again. The capacity retention rate and resistance increase rate were calculated by the following equations 1 and 2, and the results are shown in Table 1.

[0202] Equation 1: Capacity retention rate (%) = (discharge capacity after high temperature storage / initial discharge capacity) × 100

[0203] Equation 2: Resistance increase rate (%) = {(resistance after high temperature storage - initial resistance) / initial resistance} × 100

[0204] Experimental Example 2: Measurement of gas generation after high temperature storage

[0205] After the formation process was performed on the lithium secondary batteries prepared in the embodiments and comparative examples, the lithium secondary batteries were charged to 4.25V at a constant current / constant voltage of 0.33C (0.05C cutoff) at 25°C, so that the lithium secondary batteries were fully charged to 100% SOC. The fully charged batteries were stored at 60°C for 8 weeks and then transferred to a charger and discharger at room temperature (25°C). The gas collected in the bag was analyzed using a gas chromatography-thermal conductivity detector (GC-TCD), and the relative gas generation of each battery was calculated based on 100% of the gas generation measured in Comparative Example 1, as shown in Table 1 below.

[0206] Experimental Example 3: High Temperature Life Evaluation

[0207] After the formation process, the lithium secondary batteries prepared in the examples and comparative examples were charged to 4.25V at 45°C with a constant current / constant voltage (CC / CV) rate of 0.33C (0.05C cut-off) and discharged to 2.5V at a constant current (CC) rate of 0.33C.

[0208] One charge and discharge is defined as one cycle, and after the same charge and discharge is repeated 200 times, the capacity retention rate and the resistance increase rate (DCIR increase) are measured by the following equations 3 and 4. The measurement results are shown in Table 1 below.

[0209] Equation 3: Capacity retention rate (%) = (discharge capacity after 200 cycles / discharge capacity after 1 cycle) × 100

[0210] Equation 4: Resistance growth rate (%) = {(resistance after 200 cycles - resistance after 1 cycle) / resistance after 1 cycle} × 100

[0211] Experimental Example 4: Thermal Safety Assessment

[0212] After the formation process was performed on the lithium secondary batteries prepared in the examples and comparative examples, the lithium secondary batteries were charged to 4.25V at a constant current / constant voltage of 0.33C (0.05C cutoff) at 25°C, so that the lithium secondary batteries were fully charged to 100% SOC. A hot box evaluation test was performed, and the fully charged battery was heated to 140°C at a heating rate of 5°C / min, and then left to stand for 1 hour to confirm whether the battery was ignited.

[0213] The results are shown in Table 1 below, where the battery was not ignited as "passed", and the battery was ignited as "failed".

[0214] [Table 1]

[0215]

[0216] According to the results in Table 1, it can be confirmed that compared with the batteries using electrolyte solutions not containing the compound represented by Formula 1 in Comparative Examples 1 to 7, the batteries using electrolyte solutions containing the compound represented by Formula 1 in Examples 1 to 11 have better capacity and resistance characteristics after high-temperature storage, less gas generation, and better high-temperature life characteristics and safety.

[0217] In particular, even if the electrolyte solution contains a compound with a pyrazole structure, it can be confirmed that the performance of all evaluation items is significantly reduced relative to compounds such as formula Z1 in which the ester group is not substituted, formula Z2 in which a sulfonyl group (-SO2-) is substituted instead of an ester, or formula Z3 in which a carboxyl group is substituted. The reason is that since the compound represented by formula 1 contains an unshared electron pair on the ester functional group and a nitrogen bond in pyrazole, a stable film can be formed by a strong bond with the transition metal on the surface of the positive electrode, but this effect cannot be obtained for the comparative example. In addition, since the ability of the compound represented by formula 1 to move lithium is improved by the unshared electron pair of oxygen, a film that helps to improve the battery output may be formed. However, in the case of replacing the carboxyl group as in formula Z3, the same effect as in formula 1 cannot be obtained due to the acidification of the electrolyte solution and the resulting side reactions caused by the dissociation of hydrogen ions.

[0218] That is, it can be confirmed that the electrolyte solution including the compound represented by Formula 1 according to the present invention has an effect of contributing to improving high-temperature storage and high-temperature life characteristics of the lithium secondary battery.

Claims

1. A non-aqueous electrolyte solution for a lithium secondary battery, comprising: a lithium salt; an organic solvent; and a compound represented by Formula 1: [Formula 1] In Formula 1, L1 is a direct bond or an alkylene group having 1 to 10 carbon atoms, R1 is an alkyl group or a nitrile group having 1 to 10 carbon atoms, L2 is a direct bond, an alkylene group having 1 to 10 carbon atoms, an alkyleneoxy group having 1 to 10 carbon atoms, or a sulfonyl group, R2 is a fluorine-substituted or unsubstituted alkyl group, nitrile group, or isocyanate group having 1 to 10 carbon atoms, R3 is a fluorine-substituted or unsubstituted alkyl group having 1 to 10 carbon atoms, n is any integer from 0 to 2, and when n is 2, the two R3s are the same or different from each other.

2. The non-aqueous electrolyte solution for lithium secondary batteries according to claim 1, wherein R2 in Formula 1 is an alkyl group having 1 to 5 carbon atoms, a fluoroalkyl group having 1 to 5 carbon atoms, or an isocyanate group.

3. The non-aqueous electrolyte solution for lithium secondary batteries according to claim 1, wherein R3 in Formula 1 is a fluorine-substituted alkyl group having 1 to 10 carbon atoms.

4. The non-aqueous electrolyte solution for lithium secondary batteries according to claim 1, wherein The compound represented by Formula 1 is represented by Formula 1-1 or Formula 1-2: [Formula 1-1] [Formula 1-2] In Formula 1-1 and Formula 1-2, R1 to R3 are as defined in Formula 1.

5. The non-aqueous electrolyte solution for lithium secondary batteries according to claim 1, wherein Based on the total weight of the non-aqueous electrolyte solution, the amount of the compound represented by Formula 1 is 0.01 wt% to 15 wt%.

6. The non-aqueous electrolyte solution for lithium secondary batteries according to claim 1, wherein Based on the total weight of the non-aqueous electrolyte solution, the amount of the compound represented by Formula 1 is 0.05 wt% to 10 wt%.

7. The non-aqueous electrolyte solution for a lithium secondary battery according to claim 1, further comprising at least one additive selected from the group consisting of vinylene carbonate, ethylene vinyl carbonate, 1,3-propane sultone, ethylene sulfate, lithium tetrafluoroborate, lithium difluoro(oxalate)borate, and lithium difluorophosphate.

8. The non-aqueous electrolyte solution for lithium secondary batteries according to claim 1, wherein The organic solvent includes a mixture of at least two selected from the group consisting of cyclic carbonate solvents, chain carbonate solvents, and chain ester solvents.

9. A lithium secondary battery, comprising: a positive electrode comprising a positive electrode active material; a negative electrode comprising a negative electrode active material; a separator disposed between the positive electrode and the negative electrode; and the non-aqueous electrolyte solution according to claim 1.

10. The lithium secondary battery according to claim 9, wherein: The positive electrode active material includes a lithium composite transition metal oxide represented by Formula 2: [Formula 2] Li 1+x (Ni a Co b Mr c M d )O2 In Formula 2, M is at least one selected from the group consisting of W, Cu, Fe, V, Cr, Ti, Zr, Zn, Al, In, Ta, Y, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B, and Mo, and 1+x, a, b, c, and d are the atomic fractions of each independent element, wherein, -0.2 ≤ x ≤ 0.2, 0.6 ≤ a < 1, 0 < b ≤ 0.3, 0 < c ≤ 0.3, 0 ≤ d ≤ 0.1, and a + b + c + d = 1.

11. The lithium secondary battery according to claim 10, wherein: a, b, c, and d in Formula 2 respectively satisfy 0.70 ≤ a < 1, 0 < b ≤ 0.2, 0 < c ≤ 0.2, and 0 ≤ d ≤ 0.1.

Citation Information

Patent Citations

  • Moudlar multi-level converter

    KR1020220085281A

  • Smart multiple security door lock system

    KR1020230086887A